An investigation of the changes in the natural frequency of a pile affected by scour - Prendergast, L.J.; Hester, D.; Gavin, K.; O’Sullivan, J.J. (Elsevier, 2013)
Scour around bridge foundations is one of the leading causes of bridge failure. Up until recently, the monitoring of this phenomenon was primarily based around using underwater instrumentation to monitor the progression of scour holes as they develop around foundation systems. Vibration-based damage detection techniques have been used to detect damage in bridge beams. The application of these vibration based methods to the detection of scour has come to the fore in research in recent years. This paper examines the effect that scour has on the frequency response of a driven pile foundation system, similar to those used to support road and rail bridges. The effect of scour on the vibration characteristics of the pile is examined using laboratory and field testing. It is clear that there is a very clear reduction in the natural frequency of the pile as the severity of scour increases. It is shown that by combining state-of-the-art geotechnical techniques with relatively simple finite element modelling approaches, it is possible to accurately predict the natural frequency of the pile for a given scour depth. Therefore, the paper proposes a method that would allow the estimation of scour depth for a given observed pile frequency.